<span><span><span>−<span>36n</span></span>−75</span>=<span>n−65</span></span><span>−36n−75−n</span><span>=</span><span>n−65−n</span>
<span><span><span>−<span>37n</span></span>−75</span>=<span>−65</span></span><span><span><span><span>−<span>37n</span></span>−75</span>+75</span>=<span><span>−65</span>+75</span></span><span><span>−<span>37n</span></span>=10</span><span><span><span>−<span>37n</span></span><span>−37</span></span>=<span>10<span>−37
</span></span></span><span>n= <span><span>−10/</span>37 <--------- answer</span></span>
No, 1/a^b (a^-b) doesn't equal -a^b
Answer:x=11
Step-by-step explanation:
2x-13=9
2x=9+13
2x=22
x=22/2
x=11
hope this helps :)
Answer:
6%, 49%, 16%, 21%, 80%, 93%
Step-by-step explanation:
add the percent sign to each each number (6, 49, 16, 21, 80, and 93).
Answer:
(0,4)
Y =2.5X +4
Step-by-step explanation: